Demonstrating a link between diet, gut microbiota and brain: 14C radioactivity identified in the brain following gut microbial fermentation of 14C-radiolabeled tyrosine in a pig model - Murray, Margaret; Barlow, Christopher K.; Blundell, Scott; Buecking, Mark; Gibbon, Anne; Goeckener, Bernd; Kaminskas, Lisa M.; Leitner, Patricia; Selby-Pham, Sophie; Sinclair, Andrew; Waktola, Habtewold D.; Williamson, Gary; et al. (Frontiers in Nutrition, 2023)
Background: There is a need to better understand the relationship between the diet, the gut microbiota and mental health. Metabolites produced when the human gut microbiota metabolize amino acids may enter the bloodstream and have systemic effects. We hypothesize that fermentation of amino acids by a resistant protein-primed gut microbiota could yield potentially toxic metabolites and disturb the availability of neurotransmitter precursors to the brain. However, these mechanisms are challenging to investigate via typical in vitro and clinical methods. Method: We developed a novel workflow using 14C radiolabeling to investigate complex nutrient-disease relationships. The first three steps of the workflow are reported here. α-Linolenic acid (ALA) was used as a model nutrient to confirm the efficacy of the workflow, and tyrosine (Tyr) was the test nutrient. 14C-Tyr was administered to male weanling pigs fed a high resistant protein diet, which primed the gut microbiota for fermenting protein. The hypotheses were; 1) that expected biodistribution of 14C-ALA would be observed, and 2) that radioactivity from 14C-Tyr, representing Tyr and other amino acids released from resistant protein following gut microbial fermentation, would be bioavailable to the brain. Results: Radioactivity from the 14C-ALA was detected in tissues reflecting normal utilization of this essential fatty acid. Radioactivity from the 14C-Tyr was detected in the brain (0.15% of original dose). Conclusion: Metabolites of gut-fermented protein and specifically amino acid precursors to neurotransmitters such as tyrosine, are potentially able to affect brain function. By extension, resistant proteins in the diet reaching the gut microbiota, also have potential to release metabolites that can potentially affect brain function. The high specificity of detection of 14C radioactivity demonstrates that the proposed workflow can similarly be applied to understand other key diet and health paradigms.